Analysis Levels of Calcium Oxide (CaO) in Limestone from Leok Village, Biau Sub-district, Buol District - Tiwow, Vanny M. A.; Istiqomah, Almia; Abram, Hengky P.; Nurmayanti, Yuli (Jurnal Akademika Kimia, 2024)
Limestone is one of the rocks that is very abundant in Indonesia and has many benefits, especially in the field of industry. This study aims to determine the levels of calcium oxide (CaO) in limestone at Desa Leok, Kecamatan Biau, Kabupaten Buol. XRF (X-ray fluorescence) was the analytical technique utilized to ascertain the amount of calcium oxide (CaO) present in the limestone.  Both the coast area and the hill area provided samples. The measurement results indicate that the level of CaO is 92.41 % in the coast area and 93.74 % in the hill area.